1-minute integrated rain rate statistics estimated from Tropical Rainfall Measuring Mission data - Mohd Aris, Nor Azlan; Luini, Lorenzo; Din, Jafri; Lam, Hong Yin (IEEE Antennas and Wireless Propagation Letters, 2013)
This contribution presents a new model for the prediction of the 1-minute integrated Complementary Cumulative Distribution Function (CCDF) of the rain rate, P(R)1, valid for tropical and equatorial regions (specifically, latitudes ranging from 35°S to 35°N). The proposed model inherits its analytical formulation from the method currently recommended by the International Telecommunication Union – Radiocommunication Sector (ITU-R) for global P(R)1 prediction (Annex 1 of recommendation P.837-6), but it relies on Tropical Rainfall Measuring Mission (TRMM) data, in place of the ERA40 database, for the extraction of the required local meteorological inputs. With respect to the ITU-R model, the proposed model requires a lower number of inputs (2 instead of 3) and, in addition, it shows a better P(R)1 prediction performance when tested against the experimental P(R)1 curves (tropical/equatorial sites) included in the global DBSG3 database of ITU-R.